Comparison of portable emissions measurement systems (PEMS) with laboratory grade equipment - Varella, Roberto Aliandro (2018)
Real-driving emissions (RDE) testing with portable emissions measurement systems (PEMS) during the type approval and in-service conformity of light-duty vehicles was recently introduced in the European Union legislation. In this paper, three PEMS were compared with laboratory analyzers connected to the tailpipe and the dilution tunnel. The tests were conducted with two Euro 6 vehicles (one gasoline and one diesel) performing the World harmonized Light vehicles Test Cycle (WLTC) and a pre-recorded RDE cycle on a chassis dynamometer. The results showed that the differences of the PEMS gas analyzers compared to the laboratory references were typically within 2% for CO2 and 5% for NOx. The CO2 and NOx mass emissions were within 10% and 15%, respectively, with only a few exceptions. The exhaust flow rate measurements were within 10% at low speeds (urban conditions), and 5% at higher speeds. These results confirm the legislated permitted tolerances and the 2017 PEMS uncertainty estimates.